Satisfação conjugal e a sua relação com amor, personalidade e satisfação de vida - Silvano, Maiala Bittencourt (2018)
This dissertation had the general objective of exploring the relationship satisfaction by predisposing factors of love, based in the Styles and Types, life satisfaction, and the personality traits. In order to do it, two clinical trials were drafted. The first article aimed to investigate marital satisfaction’s predisposing elements through Love Styles and Types, Personality Traits, and Life Satisfaction. There was a significant correlation between the Eros love style, the Intimacy and Passion types of love, the Socialization and Openness personality traits, and Life Satisfaction and Relationship Satisfaction. The second article investigated the correlation between Love Styles and Types, Personality Traits, and Life Satisfaction and Relationship Satisfaction in different age ranges: Adolescent, intermediate Adult, and Elderly. The main results indicate that conjugal satisfaction has a positive correlation with Eros and Life Satisfaction in all age groups. Both studies had 297 participants with relationships of at least 6 months. Participants answered to: love styles scale (LAS), Sternberg Triangular Love Scale (STLS), Bateria Fatorial da Personalidade (BFP), Scales of Satisfaction with Life (SWLS) and Factorial Scale of Satisfaction in Couple Relationships. The findings revealed how important are studies that aim to assess the predisposing variables of relationship satisfaction, whereas the last is not a solid construct, because it is modulated by different phases of the cycle of life.